1982
DOI: 10.1111/j.1502-3885.1982.tb00541.x
|View full text |Cite
|
Sign up to set email alerts
|

A depositional model for stratigraphic complexes and facies superimposition in lodgement tills

Abstract: 1Y82 1201: A depositional model for stratigraphic complexes and facies superimposition in lodgement tills. Boreas. VOI. 11,. OSIO. ISSN 0300-9483.A typical stratigraphy below a streamlined till plain in Northumberland, England, consists of cross-cutting lodgemcnt till units, within and between which occur repeated shoestring interbeds of 'cut and fill' channels. I i I I units have erosional lower contacts; in certain cases marked changes in erratic content and local ice flow direction arc evident from one till… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(45 citation statements)
references
References 44 publications
5
40
0
Order By: Relevance
“…The channels formed at the ice/bed interface and were later buried by till accretion. This interpretation is in agreement with previous process-based research further north in Northumberland (Eyles et al 1982). This type of distributed subglacial drainage system is inefficient, and can result in low energy flows and ponding beneath the ice sheet.…”
Section: Lithofacies Association 2: a Subglacial Traction Till With Hsupporting
confidence: 92%
See 1 more Smart Citation
“…The channels formed at the ice/bed interface and were later buried by till accretion. This interpretation is in agreement with previous process-based research further north in Northumberland (Eyles et al 1982). This type of distributed subglacial drainage system is inefficient, and can result in low energy flows and ponding beneath the ice sheet.…”
Section: Lithofacies Association 2: a Subglacial Traction Till With Hsupporting
confidence: 92%
“…These were inferred to have originated from the glacier sole, dropping from the roof of the channel. Eyles et al (1982) argued that variable palaeo-discharges were the result of ponding episodes, possibly resulting from the closure of the channel downstream by ice or deformation of the till bed. The tills and glaciofluvial sediments were all deposited during a single, complex, episode of wet-based subglacial sedimentation (Eyles et al 1982).…”
mentioning
confidence: 99%
“…This deformation interval is proposed to represent a glaciotectonized substrate. Such local tectonization has been documented with recent and Pleistocene glacial successions (Eyles et al, 1982;Benn and Evans, 1998) and is uncharacteristic of debrisfl ow deposits.…”
Section: Glacigenic Facies Interpretationsmentioning
confidence: 95%
“…Many researchers have investigated till internal structure in terms of clast fabrics (e.g., Holmes, 1941;Harrison, 1957;Krueger, 1970;Evenson, 1971;Mark, 1974;Lawson, 1979;May et al, 1980;Dowdeswell et al, 1985;Dowdeswell and Sharp, 1986;Hart, 1994;Benn, 1995;Benn and Evans, 1996;Hicock et al, 1996;Bennett et al, 1999;Hooyer and Iverson, 2000;Carr and Rose, 2003), bed limits (Virkkala, 1952;Kjaer and Krü ger, 1998;Kjaer et al, 2003;RuszczynskaSzenajch et al, 2003), the presence of stratified subfacies units and intraclasts (Eyles et al, 1982), glaciotectonic structures (Slater, 1926;Berthelsen, 1978;Brodzikowski and van Loon, 1980;Aber, 1988;van der Meer et al, 1999), and structures associated with melt-out tills (Lawson, 1981;Shaw, 1977Shaw, , 1982. Miller (1884) probably was the first to recognise the tendency for clasts to be preferentially oriented in the direction of ice movement.…”
Section: The Internal Architecture Of Tillsmentioning
confidence: 98%
“…Later examination of tills revealed that sorted and stratified units were commonplace in many tills and it was suggested that they are linked to the mechanics of till formation (cf. Menzies, 1981;Eyles et al, 1982;Brodzikowski and Van Loon, 1987).…”
Section: The Internal Architecture Of Tillsmentioning
confidence: 98%